(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The research on innovation had been a vast field that have drawn a lot of thinking and also creativity. The condition necessary for forming a favorable environment in the most of organisation is just a light reflecting to the proposed pathway a company can utilize so as to attaining success in innovation. Innovation according to Austrian Economist Joseph Schumpeter outlined in (The theory of economic development) where he proposed 5 types of innovation. Product, Process, Business, Source of supply, Mergers and divestment.There have been alot of works on innovation which lead to addition types of innovation. To understand the topic innovation, one must be able to also comprehend the some key components of innovation, the nature of innovation, the importance, the stages of Innovation, the categories innovation, the drivers of innovation. The strategies that we can use to motivate members is also neccessary.Further, an extensive research was conducted that lead to the proponent of six conditions that can favour the management of innovation in organisations as: The importance of teamwork and the involvement of every employee, the importance of management participation, the importance of effective communication and information flow, the importance of an innovative culture, the importance of the employees vocational training, the importace of employees role integration around specialties and process rather than department.